PEMBERDAYAAN PENGGERAK PKK MELALUI PENGEMBANGAN KERAJINAN SAMPAH NON-ORGANIK DI DESA SANDIK KECAMATAN BATU LAYAR LOMBOK BARAT - Baiq Ismiwati; Taufik Chaidir; Ida Ayu Putri.S; Siti Sriningsih (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2021)
Zero waste is an ethical, economical, efficient and visionary goal, to guide people in changing their lifestyles and practices in imitation of a sustainable natural cycle, where all materials that are no longer used are designed to be a resource for others to use (en. m.wikipedia.org). Problems related to waste in Sandik Village are: 1. Non-organic waste is relatively widely scattered in the Sandik Village environment; 2. The waste bank is not yet operational; 3. People do not know much about non-organic waste which can be used as raw material for creative products that have a selling value; 4. The Sandik Village PKK Team does not have the skills to process non-organic waste into handicraft products with economic value. The aim of this service is to empower the Sandik Village PKK Driving Team in processing non-organic waste into goods that have economic value. The service method is carried out with lectures, discussions, and technical training on processing non-organic waste into products with sale value. The results of the activity: there were several participants who were able to make products at the end of the training; Participants were willing and enthusiastic to pass it on to other mothers around the village. It can be concluded that this service activity was successful, as shown by: Participants were able to sort between organic and non-organic waste and increased participants' knowledge about some of the non-organic waste that they produce every day can be used and processed into useful and economic value items